Dermatitis Atopik (DA) dan faktor-faktor yang berpengaruh di Desa Panusupan, Kecamatan Cilongok, Kabupaten Banyumas - Andina, Aning Fara; Septioni Bangun, Sugiharto; Yuniarno, Saudin (TROPHICO: Tropical Public Health J., 2025)
Atopic dermatitis is often considered a common skin problem, that has a high prevalence of cases. Panusupan Village, one of the working areas of the Cilongok II Public Health Center, has the highest number of cases of Atopic Dermatitis, which is 89 cases in 2024. The purpose of this research was to know the factors that affect the incidence of atopic dermatitis in Panusupan Village, Cilongok District. Quantitative research used a control case design. The research sample were 123 people (41 cases and 82 controls). Case data was obtained from the Cilongok II Public Health Center from January to September 2024. The variables studied included family history of allergies, temperature, smoking behavior, food allergies, and stress. The Data were analysed by univariate, bivariate, and multivariate analysis. The results of the research showed that related factors (p-value < 0.05), namely family allergy history, temperature, and food allergies, unrelated variables (p-value > 0.05), namely smoking behavior and stress. Factors that affect the incidence of atopic dermatitis are family allergy history and temperature. Recommendations that can be made are to conduct counseling related to atopic dermatitis and routinely apply moisturizer for people with atopic dermatitis.